2017
DOI: 10.1016/j.stemcr.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Signatures and Molecular Subtypes of Glioblastoma: The Role of Extracellular Transfer

Abstract: SummaryDespite the importance of molecular subtype classification of glioblastoma (GBM), the extent of extracellular vesicle (EV)-driven molecular and phenotypic reprogramming remains poorly understood. To reveal complex subpopulation dynamics within the heterogeneous intratumoral ecosystem, we characterized microRNA expression and secretion in phenotypically diverse subpopulations of patient-derived GBM stem-like cells (GSCs). As EVs and microRNAs convey information that rearranges the molecular landscape in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 20 publications
2
52
0
Order By: Relevance
“…In contrast, the mesenchymal subgroup mainly occurred in hypoxic tumor areas, such as pseudopalisading regions or the cellular tumor core. These findings uncovered a spatial dominance of expression subgroups within the GBM environmental landscape (35).…”
Section: Tumor Landscape Is Marked By Regional Differences In Transcrmentioning
confidence: 82%
“…In contrast, the mesenchymal subgroup mainly occurred in hypoxic tumor areas, such as pseudopalisading regions or the cellular tumor core. These findings uncovered a spatial dominance of expression subgroups within the GBM environmental landscape (35).…”
Section: Tumor Landscape Is Marked By Regional Differences In Transcrmentioning
confidence: 82%
“…The diversity of transcriptomic profiles observed in glioma cells is mirrored in the EVs derived from these cells. This dynamic EV mediated communication via the transfer of oncogenic proteins, mRNA and miRNA is one of the crucial factors in GBM proliferation and survival (8,9).…”
Section: Glioma Evs Enhance Tumor Proliferation and Survival In Recipmentioning
confidence: 99%
“…It was shown that the intratumoral exchange of miRNA could augment the heterogeneity of patient-derived GSCs. This was reflected in highly heterogeneous profile of miRNA expression in GBM subtypes (88). Moreover, it was reported that the expression of the subtype-enriched miRNAs such as miR-128 within transcriptionally and phenotypically diverse subpopulations of patientderived GSCs is a potent mechanism of bidirectional transitions between GBM subpopulations (89).…”
Section: Networking Between Stem-like Cells' Subpopulations: Heterogementioning
confidence: 99%